A technique for placement of apical MTA plugs using modified Thermafil carriers for the filling of canals with wide apices. (9th November 2012) - Giovarruscio, M.; Uccioli, U.; Malentacca, A.; Koller, G.; Foschi, F.; Mannocci, F.
Abstract Aim To describe a technique for the placement of apical Mineral trioxide aggregate (MTA) plugs in canals with wide apices. Summary A novel technique to fill root canals with an apical diameter larger than 0.4 mm is presented. The technique includes three main stages; three Thermafil carriers of increasing size, previously de‐sheathed by removing the Gutta‐percha coating, are selected to engage 1, 2 and 3 mm short of the apex. Their use allows the negotiation of acute curvatures and ledged canals. Subsequently, an MTA plug matching the apical gauge is pre‐formed with a pellet block, placed and condensed using the modified carriers in sequence. The presented protocol for the management of teeth with apices of a diameter greater than 0.4 mm allows a favourable apical control of the MTA. Clinical cases completed using this methodology are presented. Key learning points MTA placement in teeth with wide apices was facilitated by using de‐sheathed Thermafil carriers, to create an appropriate seal and stable platform for Gutta‐percha backfilling or subsequent fibre post placement. The use of de‐sheathed Thermafil carriers of different sizes allows predictable placement of pre‐formed MTA plugs. Gauging of Thermafil carriers enhances control of the condensation phase to limit the extrusion of MTA.